2022
DOI: 10.1021/acs.iecr.2c00283
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Biocompatible MOFs for the Clearance of Indoxyl Sulfate Using GCMC Simulations

Abstract: Indoxyl sulfate is a typical protein-bound uremic toxin, which is related to chronic kidney disease and a series of adverse effects such as cardiovascular and cerebrovascular diseases. Currently, there is still no effective method to specifically remove protein-bound urinary toxins. In this work, potential, highperformance, biocompatible metal−organic frameworks (MOFs) for adsorbing indoxyl sulfate were screened on a large scale. Then, the uptakes of indoxyl sulfate in some selected MOFs were calculated using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…The structures of five common bio-MOFs, BEPNIV, BEPPIX, KEXDIB, OREZES, and YUVSUE, were identified as promising candidates for urea/water and creatinine/water infinite dilution separations [ 115 ]. In addition, Li et al conducted a comprehensive screening of bio-MOFs with high efficiency in adsorbing IS and utilized the GCMC model to calculate the adsorption capacity of the selected MOFs for IS [ 119 ]. The results showed that aromatically coordinated MOFs with both carboxylic acid groups and metal clusters performed best on IS adsorption (>2100 mg/g).…”
Section: Application Of Mofs In Kidney Disease Treatmentmentioning
confidence: 99%
“…The structures of five common bio-MOFs, BEPNIV, BEPPIX, KEXDIB, OREZES, and YUVSUE, were identified as promising candidates for urea/water and creatinine/water infinite dilution separations [ 115 ]. In addition, Li et al conducted a comprehensive screening of bio-MOFs with high efficiency in adsorbing IS and utilized the GCMC model to calculate the adsorption capacity of the selected MOFs for IS [ 119 ]. The results showed that aromatically coordinated MOFs with both carboxylic acid groups and metal clusters performed best on IS adsorption (>2100 mg/g).…”
Section: Application Of Mofs In Kidney Disease Treatmentmentioning
confidence: 99%
“…A similar approach was used to select six out of 354 MOFs with high uptake of indoxyl sulphate, a protein-bound UT. 20…”
Section: Introductionmentioning
confidence: 99%
“…A similar approach was used to select six out of 354 MOFs with high uptake of indoxyl sulphate, a protein-bound UT. 20 Covalent organic frameworks (COFs) are based on covalently bound organic building blocks. The stability of COFs in water under extreme conditions of temperature and pH has been demonstrated experimentally.…”
mentioning
confidence: 99%